2022
DOI: 10.1007/s40520-022-02190-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rapamycin and its analogues on age-related musculoskeletal diseases: a systematic review

Abstract: Background Preclinical studies have shown a therapeutic role of the mechanistic/mammalian target of rapamycin complex 1 (mTORC1) inhibition with rapamycin and its analogues (rapalogues) on several age-related musculoskeletal disorders (MSKD). However, the applicability to humans of these findings is unknown. Objective To assess the efficacy of rapalogues on age-related MSKD in humans. Methods We conducted a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Some studies have suggested that there are mechanisms in common between epilepsy and ASD, such as the hyperactivation of mTOR signaling through genetic mutations; this signaling pathway is related to the control of cell growth and was discovered based on rapamycin, which works as an inhibitor of this pathway and is used in the control of some pathologies, such as rheumatoid arthritis and atherosclerosis. A study with animal models showed that rapamycin exhibited positive results in individuals with ASD and epilepsy [186][187][188][189]. In addition to this, another relationship was observed between ASD and epilepsy, i.e., the absence or low signaling of the GABAergic marker, which causes an imbalance in the cerebral cortex of humans, as well as in animal models [187].…”
Section: Risk Factors and Comorbidities Related To Epilepsy And Aed T...mentioning
confidence: 96%
“…Some studies have suggested that there are mechanisms in common between epilepsy and ASD, such as the hyperactivation of mTOR signaling through genetic mutations; this signaling pathway is related to the control of cell growth and was discovered based on rapamycin, which works as an inhibitor of this pathway and is used in the control of some pathologies, such as rheumatoid arthritis and atherosclerosis. A study with animal models showed that rapamycin exhibited positive results in individuals with ASD and epilepsy [186][187][188][189]. In addition to this, another relationship was observed between ASD and epilepsy, i.e., the absence or low signaling of the GABAergic marker, which causes an imbalance in the cerebral cortex of humans, as well as in animal models [187].…”
Section: Risk Factors and Comorbidities Related To Epilepsy And Aed T...mentioning
confidence: 96%
“…Established drugs that modify human muscle ageing are limited, and importantly, many of these drugs display variable therapeutic efficacy and associate with harmful side‐effect profiles that render them inappropriate for long‐term clinical use. For example, rapamycin holds variable efficacy against sarcopenia indices across health and disease 8 but is a potent immunosuppressant 9 unsuitable for chronic use in otherwise healthy humans. Drug identification efforts might instead focus on repurposing existing clinically approved compounds for sarcopenic indications as a realistic, immediately employable approach to therapeutic discovery.…”
Section: Introductionmentioning
confidence: 99%